2005
DOI: 10.1111/j.1467-8683.2005.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Insider Ownership Structure and Firm Performance: a productivity perspective study in Taiwan's electronics industry

Abstract: In the context of agency theory (Jensen and Meckling, 1976. "Journal of Financial Economics", 3, 305-360), how insider stock ownership relates to firm performance is explored in this paper. The relevant performance measure used is total factor productivity. Insiders are classified into executives, board members and blockholders so as to facilitate a detailed study. Five-year (1996-2000) panel data of 333 Taiwanese listed electronics firms are examined. It is observed that total insider ownership remains steady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…The other proxy, which does not exist in most emerging economies, is value differences among multiple classes of shares (DeAngelo & DeAngelo, 1985;Lease, McConnell, & Mikkelsen, 1984;Rydqvist, 1987). 2 Other studies that use the indirect approach include Bertrand, Mehta, and Mullainathan (2002) and Selarka (2005) on India, Song, Ali, and Pillay (2007) on Malaysia, Bae, Kang, and Kim (2002) on South Korea, Delios, Wu, and Zhou (2006) and Sheu and Yang (2005) on Taiwan, and Mitton (2002) and Lins (2003) on Indonesia, the Philippines, Sri Lanka, Thailand, and others. cash rights in the controlled affiliates (Almeida & Wolfenzon, 2006;Levy, 2009;Morck et al, 2005;.…”
Section: Background and Theory Developmentmentioning
confidence: 99%
“…The other proxy, which does not exist in most emerging economies, is value differences among multiple classes of shares (DeAngelo & DeAngelo, 1985;Lease, McConnell, & Mikkelsen, 1984;Rydqvist, 1987). 2 Other studies that use the indirect approach include Bertrand, Mehta, and Mullainathan (2002) and Selarka (2005) on India, Song, Ali, and Pillay (2007) on Malaysia, Bae, Kang, and Kim (2002) on South Korea, Delios, Wu, and Zhou (2006) and Sheu and Yang (2005) on Taiwan, and Mitton (2002) and Lins (2003) on Indonesia, the Philippines, Sri Lanka, Thailand, and others. cash rights in the controlled affiliates (Almeida & Wolfenzon, 2006;Levy, 2009;Morck et al, 2005;.…”
Section: Background and Theory Developmentmentioning
confidence: 99%
“…Sheu & Yang, 2005;Bozec & Dia, 2007;Destefanis & Sena, 2007;Lin et al, 2009;& Garcia-Sanchez, 2010). This is because the main element of business organization is its operation function which refers to the transformation of inputs into outputs, and wherein efficiency is very significant (Sheu & Yang, 2005).…”
Section: Firm Performance Importancementioning
confidence: 99%
“…Nevertheless, no specific Recently, special attention has been dedicated to determining the corporate governance effectiveness through different measurement of firm performance, one that is related to the production process, namely technical efficiency (e.g. Sheu & Yang, 2005;Bozec & Dia, 2007;Destefanis & Sena, 2007;Lin et al, 2009;& Garcia-Sanchez, 2010). This is because the main element of business organization is its operation function which refers to the transformation of inputs into outputs, and wherein efficiency is very significant (Sheu & Yang, 2005).…”
Section: Firm Performance Importancementioning
confidence: 99%
“…As a result, the value of the firm is below the optimum that could be achieved if the owner would act as the manager. Prior empirical study in corporate governance research has confirmed that separation of ownership and control decreases firm performance, as does a smaller percentage of equity held by management (e.g., Mehran 1995;Agrawal and Knoeber 1996;Core et al 1999;Anderson and Reeb 2003;Sheu and Yang 2005;Andres 2008). Jensen and Meckling (1976) argue that managers' natural inclination is to allocate the firm's resources in their own best interest, which may be in conflict with that of the shareholders.…”
Section: Introductionmentioning
confidence: 89%
“…Agrawal and Knoeber (1996) revealed that greater insider shareholding improves firm performance measured by Tobin's Q. Sheu and Yang (2005) have shown that higher equity ownership of top executive officers increases technical efficiency in Taiwanese high-tech firms. Andres (2008) reported that a firm with large family ownership performs better than firms with other block-holder ownerships, because agency costs can be reduced as the owner and manager roles are in a single hand (or, at least, on close distance by having family members as managers).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 97%